2021
DOI: 10.1002/cdq.12245
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Identity Resources in Emerging Adulthood: Associations With Facets of Dispositional Mindfulness

Abstract: The processes of career development and forming a crystallized identity can be fraught with emotional turmoil. One multidimensional construct known to reduce emotional reactivity is dispositional mindfulness (DM). We used canonical correlation analysis to examine relationships involving measures of resources for establishing a vocational identity (Hirschi, 2012a) and facets of DM in emerging adults (134 women, 38 men). Observing, describing, and nonreactivity to inner experiences contributed uniquely to the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In China, college students have more free time to use the Internet compared to middle school students, and thus are at a higher risk of being exposed to cyberbullying behavior which can lead to depression ( 24 ). In addition, several studies have shown that impending adulthood is a period of emotional complexity during which one develops career and social orientations, enters into adult relationships, and faces potentially high levels of stress due to familial, financial, and professional obligations ( 25 , 26 ) as well as frequently experiencing emotional turmoil ( 27 ). Indeed, the college years coincide with this period, thus leading to a potentially higher prevalence of depression.…”
Section: Discussionmentioning
confidence: 99%
“…In China, college students have more free time to use the Internet compared to middle school students, and thus are at a higher risk of being exposed to cyberbullying behavior which can lead to depression ( 24 ). In addition, several studies have shown that impending adulthood is a period of emotional complexity during which one develops career and social orientations, enters into adult relationships, and faces potentially high levels of stress due to familial, financial, and professional obligations ( 25 , 26 ) as well as frequently experiencing emotional turmoil ( 27 ). Indeed, the college years coincide with this period, thus leading to a potentially higher prevalence of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Как правило, осознание своих склонностей или предрасположенностей снижает стресс, невротизм, гнев, депрессию. Модель, предложенная авторами, включает несколько компонентов, при этом наиболее важным для профессиональной (само)ориентации и выбора будущего является свободное и безоценочное описание своих личностных качеств и осознание их [32]. Таким образом, осознание своих склонностей ведет к большей саморефлексии, снижает стресс и тревожность, способствует позитивному формированию профессиональной идентичности.…”
Section: влияние новой социально-экономической и культурной ситуации ...unclassified
“…Having left the dependency of childhood and adolescence, and having not yet entered the enduring responsibilities that are normative in adulthood, emerging adults often explore a variety of possible life directions in love, work, and worldviews [ 1 ]. In addition, some research suggests that the emerging adulthood is an emotionally complex period during which people develop careers and niches in society, enter adult relationships, and encounter potentially high levels of stress because of family, financial, and career obligations [ 2 , 3 ], as well as often experience emotional turmoil [ 4 ]. It is, therefore, important to help emerging adults express more positive emotions and vent negative affect properly to increase their ability to deal with life’s pressure and challenges.…”
Section: Introductionmentioning
confidence: 99%